2021
DOI: 10.1109/jiot.2021.3063549
|View full text |Cite
|
Sign up to set email alerts
|

A Noncontact Ballistocardiography-Based IoMT System for Cardiopulmonary Health Monitoring of Discharged COVID-19 Patients

Abstract: We developed a ballistocardiography (BCG)-based Internet of medical things (IoMT) system for remote monitoring of cardiopulmonary health. The system composes of BCG sensor, edge node, and cloud platform. To improve computational efficiency and system stability, the system adopted collaborative computing between edge nodes and cloud platforms. Edge nodes undertake signal processing tasks, namely approximate entropy for signal quality assessment, a lifting wavelet scheme for separating the BCG and respiration si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 35 publications
0
19
2
Order By: Relevance
“…The last one was excluded because the study did not report HRV parameters [ 36 ]. Finally, 11 studies in 12 documents [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ] were included in this review, of which, Mekhael et al [ 45 ] (journal article) and Dagher et al [ 48 ] (conference abstract) reported different outcomes for the same study. In dealing with these two documents, we described characteristics and assessed methodological quality based on Mekhael et al [ 45 ], but we extracted HRV parameters from Dagher et al [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…The last one was excluded because the study did not report HRV parameters [ 36 ]. Finally, 11 studies in 12 documents [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ] were included in this review, of which, Mekhael et al [ 45 ] (journal article) and Dagher et al [ 48 ] (conference abstract) reported different outcomes for the same study. In dealing with these two documents, we described characteristics and assessed methodological quality based on Mekhael et al [ 45 ], but we extracted HRV parameters from Dagher et al [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Before and during the 10 min period of the vital signs collection, all subjects did not have any exercise and kept the fixed positions. The recorded data are involved the non-contact sensing device and the echocardiography, where the collected vial signs contain the information of both the BCG and the respiratory effort from the head and necks of the subjects ( Liu et al., 2021 ). After the data acquisition, some professional cardiologists made the HF diagnosis by the echocardiography signals, and other recorded data was selected by the above results.…”
Section: Methodsmentioning
confidence: 99%
“…Among them, recordings were evenly distributed from each subject to ensure no bias in the data and furthermore the universality of the experimental results. In the traditional studies, the HF diseases can be easy detected by the typical waveforms of the BCG signals ( Carlson et al., 2020 ; Liu et al., 2021 ). However, the corresponding BCG signals are usually irregular in rhythm and morphology due to disordered cardiac movement (HF patients with LVEF 49 and GLS 20 ) ( Siniorakis et al., 2018 ; Hamazaki et al., 2019 ; McDonagh et al., 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially in COVID-19 pandemic since 2020, the urgent and widespread need for care, coupled with the challenge of physical distancing, has accelerated the creation and adoption of new digital technologies, as well as new processes to support their adoption and implementation across healthcare [10][11][12]. The potential benefits of IoMT can be seen within a hospital setting, where monitoring COVID-19 patients is costly in terms of time and PPE (personal protective equipment) consumption [13]. IoMT technologies enable medical devices to send data to medical practitioners who can monitor a patient's condition without having to take readings at the bedside.…”
mentioning
confidence: 99%